VALIDATION OF THE PORTUGUESE VERSION OF THE ‘TEACHERS PERCEPTIONS ABOUT THE PROFESSION’ QUESTIONNAIRE - Batista, Paula; Sousa, Tiago; Amaral-da-Cunha, Mariana; Marques, Elisa (IJRDO- Journal of Educational Research, 2017)
The aim of this study is to validate the Portuguese version of the questionnairedeveloped by (Gilat, Kupferberg, & Sagee, 2006) and adapted by (Ezer, Gilat, & Sagee,2010)), about the perceptions of preservice teachers in the training process experiencedand its contribution to their professional life - Teachers Perceptions about theProfession (TPP). Two hundred and fourteen students completed the TPP questionnaire(98 females and 116 males, aged between 21 and 41). Feasibility of scale items wasassessed by inspection of missing values (Dong & Peng, 2013). For exploration offactor structure, a principal component analysis (PCA) with varimax rotation wasperformed. Adequacy of the data for factor analysis was investigated with the KaiserMeyer-Olkinmeasure of sampling adequacy (KMO) and Bartlett’s test of sphericity(Field, 2009). Factors were extracted, using Kaiser’s criterion of retaining factors witheigenvalues of >1, and inspection of the scree plot (Cattell, 1966). Internal consistencyreliabilities of the scale and its subscales (extracted factors) were assessed withCronbach’s α. The results show that TPP questionnaire is a feasible, generally reliable,and valid instrument to assess perception of teacher education and professional identityamong pre-service teachers